Development of a Highly Specific and Sensitive Latex Agglutination Test for the Detection of Caprine Mycoplasmosis - P. Santhiya; Surya Sankar; V. Niranjana; V. Athira; R. T. Venkatachelapathy; M. Mini; A. Bosewell (Indian Journal of Microbiology, 2026)

Pathological and molecular characterization of infectious bronchitis virus in Kerala - B. Sruthy Chandran; Surya Sankar; V. Niranjana; Prasad Pallavi; B. Dhanush Krishna; M. Mini; P. M. Priya (VirusDisease, 2025)

Retraction notice to “Investigation of antimicrobial and anti-cancer activity of thermally sensitive SnO2 nanostructures with green-synthesized cauliflower morphology at ambient weather conditions” [Environ. Res. 245 (2024) 117878] - J. Josphin Mini; Safia Khan; M. Aravind; Thibi Mol; Aboud Ahmed Awadh Bahajjaj; H Marshan Robert; T. Kumaresubitha; Aneela Anwar; Hu Li (Environmental Research, 2025)

Metabolic alterations in moderately resistant West Coast Tall and susceptible Chowghat Orange Dwarf coconut varieties in response to exotic whitefly infestation - P. Logeshkumar; R. Nalini; M.L. Mini; S. Vellaikumar; A. Josephrajkumar; M. Murugan; M. Paramasivam (Arthropod-Plant Interactions, 2025)

Initial Vicarious Calibration of Ocean Colour Monitor Onboard EOS-06 Using Ocean Site, Kavaratti - K. N. Babu; Saurabh Tripathi; Moosa Ali; Anurag Gupta; Debojyoti Ganguly; Ankur Garg; Tushar Shukla; Pradeep Kumar Thapliyal; Rashmi Sharma; Mini Raman; M. Arul Muthiah (Journal of the Indian Society of Remote Sensing, 2025)

Sustainable development of cement-bonded particle boards using coir fiber edge trims and grain granulated blast furnace slag (GGBS): mechanical, thermal, and economic evaluations - Arya Ashok; Kiranbaalaji Senthilkumar; Karingamanna Jayanarayanan; K. M. Mini (Innovative Infrastructure Solutions, 2025)

Length-weight Relationship of Nine Species of Halfbeaks (Family: Hemiramphidae) from the Indian Coast - Toji Thomas; E M Abdussamad; K. G. Mini; K K Sajikumar (Thalassas: An International Journal of Marine Sciences, 2025)

Insights into the incidence, severity and morphometrics of the invasive Rugose Spiralling Whitefly Aleurodicus rugioperculatus Martin in coconut belts of Tamil Nadu, India - P. Logeshkumar; R. Nalini; A. Josephrajkumar; P. Chandramani; M. L. Mini; R. Durai Singh; K. Venkatesh; M. Murugan (International Journal of Tropical Insect Science, 2024)

Rapid Decline of SARS-CoV-2 Viral Load in Single vs. Double-Dose (Short-Interval <6 Weeks) ChAdOx nCoV-19 Vaccinated Health-Care Workers - Arnab Ghosh; Poonam Kanta; Manisha Ramola; Ritin Mohindra; Kapil Goyal; Roop Kishore; Vikas Suri; P. V. M. Lakshmi; Chanderkanta Chauhan; Manisha Sharma; Partha Rakshit; Kalaiarasan Ponnusamy; et al. (Current Microbiology, 2024)

RETRACTED: Investigation of antimicrobial and anti-cancer activity of thermally sensitive SnO2 nanostructures with green-synthesized cauliflower morphology at ambient weather conditions - J. Josphin Mini; Safia Khan; M. Aravind; Thibi Mol; Aboud Ahmed Awadh Bahajjaj; H Marshan Robert; T. Kumaresubitha; Aneela Anwar; Hu Li (Environmental Research, 2024)

Untangling the taxonomic ambiguities of the spotted seerfish Scomberomorus guttatus with the description of a new species from India - Eruppakkottil M. Abdussamad; Thomas Toji; Amalraj M. R. Margaret; Kalappurakkal G. Mini; Kothanahally M. Rajesh; Pokkathappada A. Azeez; Vinothkumar Ramar; Thayichira B. Retheesh; Athikkattil M. Abbas; Ismail Shihab; Sneha M. George; Rohith Prathibha; et al. (Journal of Fish Biology, 2024)
Scomberomorus guttatus has been subjected to a series of synonym assignations over the years. Its taxonomy has been mired with ambiguities due to the greater‐than‐average morphological variations observed in samples from different regions. An integrated taxonomic revision with molecular support indicated that the species that was thought to be a single entity, in reality, is a complex of three distinct species. They are morphologically distinct with respect to the body depth and elongation, cephalic morphometry, and meristic characteristics. Otolith morphometry and phylogenetic evidence further established the taxonomic divergence within the spotted seerfish complex. The phylogenetic characteristic as indicated by the mitochondrial Cytochrome c Oxidase subunit I (COI) sequence unveiled that S. guttatus had a high intraspecific divergence of 11.1% from its two identical congeners and a divergence of 2.34% between the congeners, indicating scope for categorizing them as separate species. Based on the morphological and molecular evidence, S. guttatus is redescribed; the senior synonym Scomberomorus leopardus is resurrected as a valid species; and a new species Scomberomorus avirostrus n. sp. is described with keys for species distinction.

Satellite Epidemic of Covid-19 Associated Mucormycosis in India: A Multi-Site Observational Study - Aanchal Satija; Tanu Anand; Aparna Mukherjee; Poonam Sharma Velamuri; Kh. Jitenkumar Singh; Madhuchhanda Das; Kripa Josten; Archana Y. Keche; Nitin M. Nagarkar; Prashant Gupta; D. Himanshu; Sejal N. Mistry; et al. (Mycopathologia, 2023)

Phytochemical profiling and toxicity effect of various seaweed species against diamondback moth, Plutella xylostella L. (Lepidoptera: plutellidae) - J. Mary Lisha; G. Srinivasan; M. Shanthi; M. L. Mini; S. Vellaikumar; K. Sujatha (International Journal of Tropical Insect Science, 2023)

Multifaceted effects of seaweed extracts against cowpea aphid, Aphis craccivora Koch, by evaluating four macroalgae - Thawfeeq Ahamed J; Srinivasan G; Shanthi M; Mini M L (Journal of Applied Phycology, 2023)

Deciphering the mechanism of Trichoderma spp. consortia possessing volatile organic compounds and antifungal metabolites in the suppression of Sclerotium rolfsii in groundnut - M. Ayyandurai; R. Akila; K. Manonmani; S. Harish; M.L. Mini; S. Vellaikumar (Physiological and Molecular Plant Pathology, 2023)

A pathway for multi-stage cyclone-induced hazard tracking—case study for Yaas - Atul Kumar Varma; Neeru Jaiswal; Ayan Das; Mukesh Kumar; Nikhil V. Lele; Rojalin Tripathy; Saroj Maity; Mehul Pandya; Bimal Bhattacharya; Anup Kumar Mandal; M. Jishad; M. Seemanth; et al. (Natural Hazards, 2023)

Age and Growth Studies in Indian Oil Sardine (Sardinella longiceps) using Hard Part Microstructure, a Tool for Biological and Ecological Understanding - E. M. Abdussamad; P. Rohit; S. Ghosh; K. G. Mini; P. Shameer; N. V. Dipti; T. B. Retheesh; A. M. Abbas; A. R. Akhil; I. Shihab; A. Gopalakrishnan (Thalassas: An International Journal of Marine Sciences, 2023)

Monitoring of Harmful Algal Bloom (HAB) of Noctiluca scintillans (Macartney) along the Gulf of Mannar, India using in-situ and satellite observations and its impact on wild and maricultured finfishes - Rameshkumar. P; P.S. Thirumalaiselvan; Mini Raman; L. Remya; R. Jayakumar; M. Sakthivel; G. Tamilmani; M. Sankar; K.K. Anikuttan; N. Nandini Menon; Raju Saravanan; T.T. Ravikumar; et al. (Marine Pollution Bulletin, 2023)

SAtellite-based Marine Process Understanding, Development, Research and Applications for Blue Economy (SAMUDRA): A Technology Demonstration Program in the Bay of Bengal - Rashmi Sharma; Neeraj Agarwal; Ratheesh R; Surisetty VVArun Kumar; A. D. Rao; KVSR Prasad; Jaya Kumar Seelam; R. Mani Murali; V. Suneel; Surendra Singh K; R. K. Sarangi; Soba J. Kizhakudan; et al. (Journal of the Indian Society of Remote Sensing, 2023)

Early detection of heavy rainfall events associated with the monsoon in Kerala, India using GPS derived ZTD and PWV estimates: A case study - M S Rose; P S Sunil; Johnson Zacharia; K M Sreejith; S Sunda; V K Mini; A S Sunil; K Vijay Kumar (Journal of Earth System Science, 2023)

Surface contamination by SARS-CoV2 RNA in dedicated COVID care area of a tertiary care hospital in North India - Subhabrata Sarkar; Arnab Ghosh; Ritin Mohindra; Linta Thomas; Devender Yadav; Harish Chand Kandpal; Manisha Biswal; P. V. M. Lakshmi; Vikas Suri; Vipin Koushal; Pankaj Malhotra; R. K. Ratho; et al. (VirusDisease, 2022)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Detection and molecular characterization of rotavirus of pigs in Kerala, India - G. Logeshwaran; Chintu Ravishankar; D. Nandhakumar; Stephy Rose Sebastian; R. Rajasekhar; K. Sumod; Binu K. Mani; E. D. Benjamin; T. R. Jayakrishnan; Koshy John; M. Mini (VirusDisease, 2020)

Using crop growth model stress covariates and AMMI decomposition to better predict genotype-by-environment interactions - R. Rincent; M. Malosetti; B. Ababaei; G. Touzy; A. Mini; M. Bogard; P. Martre; J. Le Gouis; F. van Eeuwijk (Theoretical and Applied Genetics, 2019)

Pharmaceutical products as emerging contaminant in water: relevance for developing nations and identification of critical compounds for Indian environment - Prakash Chinnaiyan; Santosh G. Thampi; Mathava Kumar; K. M. Mini (Environmental Monitoring and Assessment, 2018)

First report of detection and molecular characterization of porcine parvovirus in domestic and wild pigs in Kerala, India - J. Aishwarya; Chintu Ravishankar; R. Rajasekhar; K. Sumod; Nimisha Bhaskar; Shiju Shaji; Koshy John; M. Mini (VirusDisease, 2016)

Representative archaeological finds of pietra ollare from Comacchio (Italy): identifying provenance and high-T mineral breakdown reactions hindering lithotype classification - Francesco M. Mini; Patrizia Santi; Alberto Renzulli; Maria P. Riccardi; Fabrizio Antonelli; Antonio Alberti (Archaeological and Anthropological Sciences, 2016)

Molecular typing and phylogenetic analysis of classical swine fever virus isolates from Kerala, India - Nimisha Bhaskar; Chintu Ravishankar; R. Rajasekhar; K. Sumod; T. G. Sumithra; Koshy John; M. Mini; Reghu Ravindran; Shiju Shaji; J. Aishwarya (VirusDisease, 2015)

Bio-optic characterization of Discosphaera tubifer bloom occurs in an overcrowded fishing harbour at Veraval, India - Subir Kumar Mandal; Vipul R. Patel; Ganesh Temkar; Basil M. George; Mini Raman (Environmental Monitoring and Assessment, 2015)

Species identification of mixed algal bloom in the Northern Arabian Sea using remote sensing techniques - R. Dwivedi; M. Rafeeq; B. R. Smitha; K. B. Padmakumar; Lathika Cicily Thomas; V. N. Sanjeevan; Prince Prakash; Mini Raman (Environmental Monitoring and Assessment, 2015)

Isolation and Characterization of Pasteurella multocida from Poultry and Deer - Thulasi G. Pillai; K. Indu; R. Rajagopal; M. Mini; G. Krishnan Nair; Koshy John; Siju Joseph (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

Motoneuron model of self-sustained firing after spinal cord injury - Mini Kurian; Sharon M. Crook; Ranu Jung (Journal of Computational Neuroscience, 2011)

An approach to compute Photosynthetically Active Radiation using IRS P4 OCM - S. K. Singh; Mini Raman; R. M. Dwivedi; S. R. Nayak (International Journal of Remote Sensing, 2008)

Identification of Novel Superior Polycationic Vectors for Gene Delivery by High-throughput Synthesis and Screening of a Combinatorial Library - Mini Thomas; James J. Lu; Chengcheng Zhang; Jianzhu Chen; Alexander M. Klibanov (Pharmaceutical Research, 2007)